'Lihaaf': A Story of the Story. (March 2014) - Priyadarshini, Anamika
The common understanding of South Asian women's identity is usually derived from the conventional perception that envisions the 'third world' woman as a submissive victim of barbaric machismo. South Asian scholars, especially feminists, have been challenging this monolithic image and trying to throw light on the various complex layers that define women in the so-called 'third world'. They are focusing, instead, on the living reality of the dynamic woman with a body, mind and desires who cannot be shackled into the frame of victimised/sacrosanct mother. 'Lihaaf'—a story about two women's erotic relationship; published in 1942; written by an Indian Muslim woman—becomes critical to this evolving understanding. This article is an analysis of the various narratives of the publication of 'Lihaaf' which left a deep impact on the author Ismat Chughtai's life and also on the history of Urdu literature and the heritage of literary work on homosexuality. These narratives recognise 'Lihaaf' as a stand that reflects on a more realistic aspect of Indian women, who can be more than a Mother, who does not necessarily follow the script of the master narrative.